Exploring the Impact of Moral Intelligence on Psychological Resilience among High School Students: A Case Study - Hassan, Ahmed K.; Amira, Mostafa Samy; Naif, Albujulaya; Frikha, Mohamed; Alyousef, Ammar; Bursais, Abdulmalek K. (Journal of Posthumanism, 2025)
The study investigates how moral intelligence helps high school students in Al-Ahsa Saudi Arabia stay psychologically resilient. The project was completed with 425 male and female students by measuring their moral intelligence and psychological resilience across its four important areas using two scales. Results indicated that most participants had average moral intelligence but did better with being attentive and accepting than they did with dealing with criticism and fostering respectful behavior. On average, participants’ psychological resilience was moderate and those who had stronger religious values found it simpler to manage stress. Still, many caregivers reported a lack of social support, indicating that further support in this area could be very useful. There were differences between the genders and females did well on tasks related to justice, while males were stronger in social skills. The researchers discovered that strong moral intelligence is related to healthy psychological resilience and that religion and moral traits like empathy and fairness make it easier for people to manage stress. The results suggest that special efforts are needed to improve respect and social networks at school. More studies ought to assess these relationships in many different settings and study whether they continue over the long term, as well as how moral intelligence develops in various educational environments. These investigations will show us how resilience and moral intelligence are influenced by culture and circumstances.